2021
DOI: 10.1029/2021gl095655
|View full text |Cite
|
Sign up to set email alerts
|

Connection Between Foreshock Structures and the Generation of Magnetosheath Jets: Vlasiator Results

Abstract: Earth's magnetosheath forms the interface between our planetary magnetosphere and the supermagnetosonic solar wind flow. The magnetosheath is bounded by the bow shock separating it from the upstream solar wind, and by the magnetopause, which is the outer boundary of the magnetosphere. An important factor determining the nature of the bow shock and the magnetosheath is the orientation of the interplanetary magnetic field (IMF). Where the bow shock normal direction is quasi-parallel to the IMF, solar wind partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…Although several mechanisms have been proposed to explain how jets are generated, their origin is still not understood. Some studies have speculated on the connection of jets to upstream magnetic compressive structures (e.g., SLAMS) 25 27 . However, no direct observations have been made so far and the exact causal link has yet to be revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Although several mechanisms have been proposed to explain how jets are generated, their origin is still not understood. Some studies have speculated on the connection of jets to upstream magnetic compressive structures (e.g., SLAMS) 25 27 . However, no direct observations have been made so far and the exact causal link has yet to be revealed.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of jets has been discussed much for several years, and many of the points made in previous studies were based on the properties of jets as shown directly through particle moments (see e.g., . However, recently, as shown by simulations and observations (Raptis et al, 2022;Suni et al, 2021), jets appear to be directly connected to the foreshock dynamics for which a fluid approach and the particle moments may provide quite a limited picture (see e.g., Section 6.6 of Paschmann and Daly (1998)). Here, we show that if we consider the jet as an isolated population and perform a series of fits, it exhibits a SW-like profile.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream of the Qpar shock, jets have been associated with several other generation mechanisms, from shock ripples (Hietala et al., 2009; Hietala & Plaschke, 2013) to upstream rotational discontinuities (Archer et al., 2012; Dmitriev & Suvorova, 2012) and reconnection (Preisser et al., 2020). More recently, investigations have focused on the connection of jets to upstream foreshock structures (Karlsson et al., 2015; Omelchenko et al., 2021; Sibeck et al., 2021; Suni et al., 2021) and to the reformation of the Qpar shock (Raptis et al., 2022). While the exact generation mechanism of these structures is still under investigation, the connection to SW properties such as the cone angle and transient events has been demonstrated in various recent studies, indicating that there is a direct link between SW conditions and MSH jets (Koller et al., 2022; LaMoury et al., 2021; Plaschke et al., 2013; Tinoco‐Arenas et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…(2015) proposed that HSJs are generated by SLAMSs, a kind of upstream compressive structures with enhanced field magnitude and dynamic pressure. When the SLAMSs or other similar compressive structures penetrate through a dented part of the shock front, they maintain a higher dynamic pressure than the surrounding plasma and become HSJs (Palmroth et al., 2018; Suni et al., 2021). Other foreshock structures, for example, SHFAs (Omidi et al., 2016), and solar wind discontinuities (Archer et al., 2012; Savin et al., 2012), are also potential sources of HSJs.…”
Section: Introductionmentioning
confidence: 99%